การพัฒนาการเขียนสะกดคำในภาษาไทยของนักเรียนชั้นมัธยมศึกษาปีที่ 3 โรงเรียนศรีธรรมวิทยา อำเภอเมืองยโสธร จังหวัดยโสธร - ชูรัตน์, ณัฐธิดา; ขนฺติธมฺโม (ศิลากุล), พระมหานพรัตน์; (จิรศักดิ์ ทองหอม), พระครูเมธีธรรมบัณฑิต; มั่นจิต, รพีภัทร (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This research aims to study and compare the achievement in spelling and to promote and enhance the spelling proficiency of Grade 9 students at Srithamwitaya School, Nai Mueang Subdistrict, Mueang District, Yasothon Province. The target group for this study consisted of 62 Secondary students in the first semester of the academic year 2024. This research was conducted as a quasi-experimental study. The research findings revealed that the spelling proficiency of Grade 9 students in the first semester of the academic year 2024 at Srithamwitaya School was at a moderate level (µ = 3.47, σ = 1.88). Additionally, it was found that promoting and developing Thai reading aloud skills among these students was both effective and met the standard criteria. Furthermore, the spelling and reading practice exercises for difficult words demonstrated efficiency and learning achievement at the levels of 80.52/84.53, aligning with the set criteria.   Keywords: skill development, spelling proficiency, Thai language words, Srithamwitaya School.